PENGEMBANGAN MODUL AJAR PENDIDIKAN PANCASILA BERBASIS ARTIFICIAL INTELLIGENCE UNTUK PENGUATAN ETIKA KEWARGANEGARAAN DIGITAL SISWA SMA NEGERI 2 SUNGAI PENUH - Rahmanda Putri, Melan; Aditya Candra, Alif; Santoso, Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Artificial Intelligence-based teaching module for Pancasila Education to strengthen digital citizenship ethics among students at SMA Negeri 2 Sungai Penuh. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were students of SMA Negeri 2 Sungai Penuh. Data were collected through validation questionnaires, practicality questionnaires, and learning outcome tests in the form of pretest and posttest. The product developed is an interactive teaching module integrated with AI tools to encourage students' critical thinking and ethical responsibility in the digital environment. The validation results showed that the module achieved a very high level of validity, with a score of 97.91% from material experts, categorized as very feasible, and a score of 79.16% from media experts, categorized as feasible. The practicality test indicated a score of 82.50%, categorized as very practical, showing that the module is user-friendly and relevant to students' needs. Furthermore, the effectiveness test revealed an N-Gain score of 0.39, which falls into the moderate category, while the paired sample t-test confirmed a significant improvement in students' learning outcomes and ethical awareness. In conclusion, the developed AI-based teaching module is valid, practical, and effective in strengthening digital citizenship ethics in Pancasila Education.